The Political thought of Imam Zain al-Abidin: A Critical Analysis - Dr. Saifullah al-Azhari (Journal of Religion and Society, 2025)
Imam Zainul Abidin stayed away from politics all his life. Some political groups that emerged after the Karbala incident wanted to push him into politics, but he refused and never took part in the power struggle because he knew that there was no political role left for a person like him. Politics has its own temperament, which will not accept him. He chose a different role for himself. The same that was told for a scholar in the Qur'an i.e. Remembrance. That is to remind people that they are God's servants and one day they must appear before their Lord. He used to deliver the Friday sermon in Madinah and reminded the creatures of God's servitude to the Lord of the Universe and responsibility in the Hereafter. He knew that if someone despairs from the state, he should make society the center of all his efforts. From Imam Zainul Abideen's Caracter and role, we learn that despite the sympathy of all, he did not take up armed struggle against the ruler of the time but followed the policy of preaching good tidings, because he knew that controlling the people sitting in the halls of power through armed struggle would lead to nothing but bloodshed, as armed struggle requires a balance of power, that is possible between two states, while impossible between populace and the state. Keywords: Politics, Populace, State, Armed Struggle, Karbala Incident, Preaching